2023
DOI: 10.1002/agg2.20400
|View full text |Cite
|
Sign up to set email alerts
|

Host resistance by sowing date interaction reduced Fusarium wilt pressure and improved grain yield of chickpea (Cicer arietinum L.) in North Shoa, Ethiopia

Abstract: Chickpea Fusarium wilt is seriously damaging chickpea productivity. To determine the integrated effects of three sowing dates and four chickpea varieties on epidemics of Chickpea Fusarium wilt and grain yield, field experiments were conducted in naturally infested soils at Alem Ketema and Enewari, Ethiopia, during 2018. Treatments were factorial arranged in a randomized complete block design with three replications. Results showed that variety Mastewal recorded relatively low mean Fusarium wilt incidence at Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Variety selection and planting date adjustment are reported as effective mechanisms for reducing yield loss attributed to various diseases in chickpeas. For instance, Ali and Habtamu [ 12 ] recommended delaying the planting date and growing variety Mastewal to maximize chickpea yield and minimize the effect and progression of fusarium wilt at chickpea growing areas in north Shoa. On-station and on-field trials conducted in east Shoa indicated that the adjustment of chickpea planting to early September increased grain yield by 35 % under rainfed conditions [ [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variety selection and planting date adjustment are reported as effective mechanisms for reducing yield loss attributed to various diseases in chickpeas. For instance, Ali and Habtamu [ 12 ] recommended delaying the planting date and growing variety Mastewal to maximize chickpea yield and minimize the effect and progression of fusarium wilt at chickpea growing areas in north Shoa. On-station and on-field trials conducted in east Shoa indicated that the adjustment of chickpea planting to early September increased grain yield by 35 % under rainfed conditions [ [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%
“…Sowing date adjustment greatly varies from place to place. For instance, planting of chickpea can be done at early July in moisture-stressed lowland areas or when planted on sandy soil types [ 11 , 12 ]. In general, planting time is determined by the condition of abiotic and biotic stresses, soil type, and agroecological conditions of the target area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation